Association of BDNF and MMP-9 single-nucleotide polymorphisms with the clinical phenotype of schizophrenia - Pan, Lihong; Cao, Zhonghai; Chen, Lianghu; Qian, Min; Yan, Yuzhong (Frontiers in Psychiatry, 2022)
Objective Schizophrenia is a highly polygenic psychiatric disorder; however, the complex genetic architecture underlying the pathogenesis remains elusive. Brain-derived neurotrophic factor (BDNF), a neurotrophin, and matrix metalloproteinase 9 (MMP-9), a gelatinase B, are the promising candidate genes for schizophrenia. To shed new light on the relationship between the single-nucleotide polymorphisms (SNPs) of BDNF and MMP-9 and the clinical variability of schizophrenia phenotype, this study aims to evaluate the relationship, and provide more definitive evidence for the relationship with various clinical features of schizophrenia. Methods A case-control association study was performed, and one hundred and five subjects of Chinese Han population were enrolled, including 55 schizophrenia patients (SP) and 50 healthy controls (HC). The BDNF rs6265 196 G > A and MMP-9 rs3918242 −1562C > T SNPs were genotyped using PCR-RFLP assay. The Positive and Negative Syndrome Scale (PANSS) was used to assess the clinical symptoms of patients with schizophrenia. Results Compared with HC, the frequency of SP carrying BDNF rs6265 GG/GA genotype was significantly higher than HC, and the frequency of SP carrying BDNF rs6265 AA genotype was significantly lower than HC (p < 0.01). With regards to MMP-9 rs3918242 −1562C > T SNP, no significant difference was observed between the control and SP. BDNF GG genotype showed significantly higher PANSS and positive symptoms score than GA and AA genotypes (P < 0.01). MMP-9 CC genotype showed significantly higher PANSS and general score than CT and TT genotypes (P < 0.05). Conclusion BDNF rs6265 196 G > A and MMP-9 rs3918242–1562C > T SNPs are related to the clinical features of schizophrenia and could be a useful biomarker for the changes, remission or deterioration of clinical status of schizophrenia.